Low-dose trimethoprim-sulfamethoxazole for the treatment of Pneumocystis jirovecii pneumonia (LOW-TMP): protocol for a phase III randomised, placebo-controlled, dose-comparison trial. Issue 7 (21st July 2022) - Sohani, Zahra N.; Butler-Laporte, Guillaume; Aw, Andrew; Belga, Sara; Benedetti, Andrea; Carignan, Alex; Cheng, Matthew P.; Coburn, Bryan; Costiniuk, Cecilia T; Ezer, Nicole; Gregson, Dan; Johnson, Andrew; et al.
Abstract : Introduction: Pneumocystis jirovecii pneumonia (PJP) is an opportunistic infection of immunocompromised hosts with significant morbidity and mortality. The current standard of care, trimethoprim-sulfamethoxazole (TMP-SMX) at a dose of 15–20 mg/kg/day, is associated with serious adverse drug events (ADE) in 20%–60% of patients. ADEs include hypersensitivity reactions, drug-induced liver injury, cytopenias and renal failure, all of which can be treatment limiting. In a recent meta-analysis of observational studies, reduced dose TMP-SMX for the treatment of PJP was associated with fewer ADEs, without increased mortality. Methods and analysis: A phase III randomised, placebo-controlled, trial to directly compare the efficacy and safety of low-dose TMP-SMX (10 mg/kg/day of TMP) with the standard of care (15 mg/kg/day of TMP) among patients with PJP, for a composite primary outcome of change of treatment, new mechanical ventilation, or death. The trial will be undertaken at 16 Canadian hospitals. Data will be analysed as intention to treat. Primary and secondary outcomes will be compared using logistic regression adjusting for stratification and presented with 95% CI. Ethics and dissemination: This study has been conditionally approved by the McGill University Health Centre; Ethics approval will be obtained from all participating centres. Results will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT04851015 .